1971
DOI: 10.1029/jc076i012p02805
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric electrical discharges in the presence of water and ice particles

Abstract: A variety of electrical discharges were photographically examined in a preliminary survey of water‐involving discharge phenomena that occurred in simulations of the thunderstorm environment. The investigation was limited to situations showing no clear evidence of water drop disruption. Discharges between oppositely charged falling drops of water exhibit a luminosity distribution that suggests electron emission from the negative drop. Measurements indicate that the current density in this discharge may be 20 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This tendency has traditionally been attributed to both precipitation and the charge tapped by lightning being transported similarly, but it is also possible that the detailed microphysics of spark development in the presence of precipitation has an effect. Several investigators have observed that water particles subjected to strong electric fields produce streamers [e.g., Pišler and Atkinson , ]. Pišler and Atkinson [] found that sparks tended to connect a stream of falling drops and suggested that this was caused by streamers charging the drops and the charge then causing the particles to attract the spark.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency has traditionally been attributed to both precipitation and the charge tapped by lightning being transported similarly, but it is also possible that the detailed microphysics of spark development in the presence of precipitation has an effect. Several investigators have observed that water particles subjected to strong electric fields produce streamers [e.g., Pišler and Atkinson , ]. Pišler and Atkinson [] found that sparks tended to connect a stream of falling drops and suggested that this was caused by streamers charging the drops and the charge then causing the particles to attract the spark.…”
Section: Observationsmentioning
confidence: 99%
“…Several investigators have observed that water particles subjected to strong electric fields produce streamers [e.g., Pišler and Atkinson , ]. Pišler and Atkinson [] found that sparks tended to connect a stream of falling drops and suggested that this was caused by streamers charging the drops and the charge then causing the particles to attract the spark. Whether this process influences the propagation path of lightning in a thunderstorm is unclear. The charge had moved too far away to support continued vertical propagation, so the IS could not reach the layer of substantial charge density.…”
Section: Observationsmentioning
confidence: 99%
“…And then, the form of the drop will be an ellipsoid of revolution extended along the external field, which is more of advantage to initiate the corona emission from surface of water drop owing to the smaller radius of curvature at its two ends of long axis. Some research on the effect of electric field on the distortion and deformation of droplet and corona emission performance can be found in [14][15][16][17][18][19]. In [15], it is pointed out that positive corona can occur in the field of 2.5 kV/cm when a pair of water drops with a relative speed of 5.8 m/s and with an equivalent radius of 2.7 mm and 0.65 mm are colliding into a long filament.…”
Section: Effect Of Raindropsmentioning
confidence: 99%
“…Supposedly the cloud droplets capture the free ions, effectively lowering the number of mobile charges, and reducing the electrical conductivity. However, the high electrical field within the thunderstorm is responsible for the formation of space charge due to point discharge at the ground and assorted discharge effects from irregular particles (ice crystals) and effects during the interactions of water drops (see Dawson, 1970;Pisler & Atkinson, 1971). Hence one might expect an increase in the electrical conductivity as the field builds.…”
Section: Introductionmentioning
confidence: 99%